2023
DOI: 10.3390/ijms241310818
|View full text |Cite
|
Sign up to set email alerts
|

Talk to Me—Interplay between Mitochondria and Microbiota in Aging

Abstract: The existence of mitochondria in eukaryotic host cells as a remnant of former microbial organisms has been widely accepted, as has their fundamental role in several diseases and physiological aging. In recent years, it has become clear that the health, aging, and life span of multicellular hosts are also highly dependent on the still-residing microbiota, e.g., those within the intestinal system. Due to the common evolutionary origin of mitochondria and these microbial commensals, it is intriguing to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 203 publications
0
1
0
Order By: Relevance
“…Gut microbiota and their metabolites can regulate mitochondrial energy metabolism, ROS production, and immune-inflammatory responses by participating in the Borbolis et al (2023) and Endres and Friedland (2023) . Li et al found that butyrate can induce mitochondrial autophagy through the activation of adenylate-activated protein kinase (AMPK), thereby attenuating hydrogen peroxide- (H 2 O 2 -)induced oxidative stress, intestinal epithelial barrier damage, and mitochondrial dysfunction ( Li X. et al, 2022 ).…”
Section: A Link Between Ms and Gut Microbiotamentioning
confidence: 99%
“…Gut microbiota and their metabolites can regulate mitochondrial energy metabolism, ROS production, and immune-inflammatory responses by participating in the Borbolis et al (2023) and Endres and Friedland (2023) . Li et al found that butyrate can induce mitochondrial autophagy through the activation of adenylate-activated protein kinase (AMPK), thereby attenuating hydrogen peroxide- (H 2 O 2 -)induced oxidative stress, intestinal epithelial barrier damage, and mitochondrial dysfunction ( Li X. et al, 2022 ).…”
Section: A Link Between Ms and Gut Microbiotamentioning
confidence: 99%